Terrestrial and Martian Paleo-Hydrologic Environment Systematic Comparison with ASI PRISMA and NASA CRISM Hyperspectral Instruments - Angelo Zinzi; Paola Manzari; Veronica Camplone; Eleonora Ammannito; Giuseppe Sindoni; Francesco Zucca; Gianluca Polenta (Remote Sensing, 2025)
The comparative analysis of hyperspectral data from different instruments can provide detailed information on the composition and geology of similar environments on different planets. This study aims to compare data acquired from the PRISMA satellite, used for Earth observation, with those collected by the CRISM spectrometer onboard the Mars Reconnaissance Orbiter, orbiting Mars, in order to analyze the geological and mineralogical differences between the morphologies present on the two planets of interest. The comparison of these data will allow us to examine the mineralogical composition, highlighting the similarities and differences between the terrestrial and Martian environments. In particular, in this study, we present a method to refine the interpretation of spectral features of minerals commonly found in paleo-hydrological environments on Mars and identified also by field analysis of similar terrestrial sites, thus allowing us to improve the Martian sites’ characterization. Thanks to this approach, we have been able to find spectral similarities (e.g., band positions, band ratios) among specific Earth and Mars sites, thus demonstrating that it could be further expanded, by systematically using Earth-observation orbiting instruments to better characterize and constrain Martian spectral data.